Bayaniyyahi-yi Kumitahi-yi Markazi-yi Hizbi Dimukrati Kurdistani Iran : (Hizbi Dimukrati Kurdistan Iran)
Statement of the Central Committee of the Democratic Party of Iranian Kurdistan on the occassion of the fortieth anniversary of the founding of the Party.